Managerial Turnover in a Changing World - Garrett, Daniel F.; Pavan, Alessandro (Journal of Political Economy, 2012)
We develop a dynamic theory of managerial turnover in a world in which the quality of the match between a firm and its managers changes stochastically over time. Shocks to managerial productivity are anticipated at the time of contracting but privately observed by the managers. Our key positive result shows that the firm’s optimal retention decisions become more permissive with time. Our key normative result shows that, compared to what is efficient, the firm’s contract induces either excessive retention at all tenure levels or excessive firing at the early stages of the relationship, followed by excessive retention after sufficiently long tenure.